Effect of Activated Carbon on the Combustion Characteristics of Magnesium–Sodium Nitrate Propellants - Anceu Murniati; Arie Hardian; Zellin Azsari Arifin; Suharnoko Suharnoko; Adella Fajaretta Gunawan; Ranti Nur Aprillianti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Magnesium–nitrate-based propellant systems represent an alternative class of solid propellants whose combustion characteristics can be modified through composition and the use of additives. This study aims to evaluate the effect of activated carbon addition on the burning rate and combustion energy of magnesium–sodium nitrate– based propellants. Propellant samples were prepared in two compositional variations, namely NaNO₃/Mg and NaNO₃/Mg with activated carbon addition. The burning rate was measured experimentally with five replicates (n = 5), while the calorific value was determined using a bomb calorimeter. Differences in burning rate were analyzed using Welch’s t-test at a significance level of α = 0.05. The results show that the addition of activated carbon significantly reduces the burning rate of the propellant (p < 0.001). In contrast, the calorific value increased from 2395 cal g -1 to 2617 cal g -1 . These findings indicate that activated carbon modifies the combustion characteristics and contributes to the energetic properties of the system, suggesting its potential application for burning rate control in magnesium–sodium nitrate–based propellants.